2021
DOI: 10.1002/ps.6479
|View full text |Cite
|
Sign up to set email alerts
|

Influence of floating plant density on potential herbicide spray loss

Abstract: BACKGROUND Mesocosm experiments were conducted to evaluate the effect of floating plant density on over‐the‐top spray solution loss to the column using a tracer dye. Experiments quantified in‐water rhodamine water tracer (RWT) dye concentration after foliar treatment at 935 L ha−1 to waterhyacinth [Eichhornia crassipes (Mart.) Solms], waterlettuce (Pistia stratiotes L.) and giant salvinia (Salvinia molesta D.S. Mitchell) at 0, 25, 50 and 100% area covered (PAC). RESULTS As expected, spray loss to the water sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Canopy cover and height were strongly correlated with percent spray retention for all broadleaf weeds (Table 3). These results are consistent with those of other studies that suggested canopy height and structure influence spray interception among floating plant species (Mudge et al 2021;Sperry et al 2022).…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Canopy cover and height were strongly correlated with percent spray retention for all broadleaf weeds (Table 3). These results are consistent with those of other studies that suggested canopy height and structure influence spray interception among floating plant species (Mudge et al 2021;Sperry et al 2022).…”
supporting
confidence: 93%
“…All experiments used rhodamine WT (RWT) dye (Rhodamine WT Liquid; Keystone Aniline Corp., Chicago, IL) to approximate herbicide deposition. Doing this cost considerably less money than quantifying herbicides analytically (Mudge et al 2021; Sperry et al 2022). Use of RWT to follow trace aqueous herbicide movement has been used in a variety of field environments for decades (e.g., Fox et al 1991, 1993, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has established carrier volume directly affects spray deposition, herbicide activity, and ultimately aquatic plant control (Moreira et al 1999; Nelson et al 2007; Sperry and Ferrell 2021; Sperry et al 2022; Van et al 1986; Willard et al 1998). Limitations of high carrier volumes (e.g., 935 L ha– 1 ) include reduced spray retention at low floating plant densities, thus resulting in spray loss to the water column (Mudge et al 2021), and reduced herbicide concentration per spray droplet (Knoche 1994). In general, herbicide applications made with lower carrier volumes are preferred because of time savings when filling spray tanks (Nelson et al 2007), public perception (Sperry and Ferrell 2021), increased spray retention on plant targets (Sperry et al 2022), and the increased performance of some herbicides on floating plant species (Nelson et al 2007; Sperry and Ferrell 2021; Van et al 1986).…”
Section: Introductionmentioning
confidence: 99%